2006
DOI: 10.1016/j.jembe.2006.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Surge ammonium uptake in macroalgae from a coral atoll

Abstract: Surge (non-linear) uptake of ammonium, measured by incorporation of 15 N, was investigated in three species of macroalgae (Ulva lactuca Linnaeus (Chlorophyta), Soliera robusta (Greville) Kylin (Rhodophyta) and Dictyota dichotoma (Hudson) Lamouroux (Phaeophyta)) from Kavaratti atoll (Lakshadweep, India). Addition of ammonium (up to 20 µmol L-1) led to pronounced uptake within 4-6 min, with the amount of ammonium taken up during surge phase (<4 min) accounting for from about half to 10 times that taken up during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
1
2
0
1
Order By: Relevance
“…By contrast, the ammonium uptake rates of three seaweed species ( Ulva lactuca , Soliera robusta and Dictyota dichotoma ) showed no diurnal variation, i.e . the rates of ammonium uptake in the light were similar to the rates in the dark (Raikar & Wafar ). Surprisingly, the uptake of inorganic nitrogen in light versus darkness by seagrasses has been assessed only twice, for Zostera marina and Thalassia testudinum (Iizumi & Hattori ; Lee & Dunton ).…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…By contrast, the ammonium uptake rates of three seaweed species ( Ulva lactuca , Soliera robusta and Dictyota dichotoma ) showed no diurnal variation, i.e . the rates of ammonium uptake in the light were similar to the rates in the dark (Raikar & Wafar ). Surprisingly, the uptake of inorganic nitrogen in light versus darkness by seagrasses has been assessed only twice, for Zostera marina and Thalassia testudinum (Iizumi & Hattori ; Lee & Dunton ).…”
Section: Introductionsupporting
confidence: 72%
“…This has been shown both for phytoplankton and seaweed species (Conway et al . ; Thomas & Harrison ; Pedersen ; Dy & Yap ; Raikar & Wafar ). Initial rapid accumulation of ammonium by the leaves of the seagrass Zostera marina has also been reported (Short & McRoy ).…”
Section: Discussionmentioning
confidence: 99%
“…Glenn and Doty (1990) suggested that the absorption of nutrients during the fast flowing water among the plant canopy is higher for ammonium at a lower depth than for nitrate at the higher depth. The absorption of ammonium by seaweed is more important than nitrate (Dy and Yap, 2001;Raikar and Wafar, 2006). Similarly to DGR of K. alvarezii in first study, the second study with brown strain showed the interaction between strain and initial weight at the same depth which was highly significant (P<0.01).…”
Section: Daily Growth Ratementioning
confidence: 78%
“…Glenn dan Doty (1990) mengemukakan bahwa penyerapan unsur hara saat air mengalir cepat di antara tallus lebih tinggi untuk amonium pada kedalaman rendah daripada untuk nitrat pada kedalaman yang tinggi. Penyerapan amonium oleh rumput laut lebih penting daripada penyerapan nitrat (Dy dan Yap, 2001;Raikar dan Wafar, 2006). Gambar 2 memperlihatkan laju pertumbuhan harian strain coklat yang lebih tinggi daripada strain hijau.…”
Section: Hasil Dan Pembahasanunclassified